Same same but different: Credit risk provisioning under IFRS 9 - Markus Behn; Cyril Couaillier (European Central Bank (ECB), 2023)
We analyse the impact of the adoption of expected credit loss accounting (IFRS 9) on the timeliness and potential procyclicality of banks' loan loss provisioning. We use granular loan-level data from the euro area's credit register and investigate both firm-level credit events and macroeconomic shocks (2020 COVID-19 pandemic, 2022 energy price shock). We find that provisions under the new standard are higher before default and more responsive to shocks. However, the majority of provisioning still occurs at the time of default and the dynamics around default events are similar to pre-existing national standards. Additionally, banks with a larger capital headroom provision significantly more, particularly for loans using IFRS 9. This suggests a higher risk of underprovisioning for less capitalized banks.
Keywords: G21; G28; G32; 330; bank regulation; financial stability; loan loss accounting; credit risk